FUNCTIONAL AND ULTRASTRUCTURAL EVALUATION OF MYOCARDIAL PROTECTION PROVIDED BY INTERMITTENT CORONARY SINUS PERFUSION IN THE ISOLATED DOG HEART - Andrade, Rubens Ramos de [UNESP]; Tucci, PJF; Silva, MAM; Oliveira, R. A.; Gregorio, E. A.; Curi, P. R.; Hossne, W. S. (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
1. The protection offered by intermittent perfusion of of cardioplegic solution through the coronary sinus was investigated in isovolumic blood-perfused dog heart preparations submitted to 60 min of ischemia and 45 min of reperfusion.2. The preparations were divided into three treatment groups: a) coronary sinus, consisting of preparations (N = 10) perfused through the coronary sinus under 40 cm water pressure; b) aortic, consisting of preparations (N = 10) perfused through the aortic stump under 100 mmHg pressure; c) control, consisting of hearts (N = 9) that were not perfused with cardioplegic solution.3. Properties of contractile capacity and relaxation were markedly impaired in the control group but were preserved to a comparable extent in the groups perfused with cardioplegic solution through the aorta and coronary sinus. Developed pressure decreased in the control group (before ischemia: 70 +/- 5.5 mmHg; after reperfusion: 35 +/- 12 mmHg; P < 0.05) and didn't vary in the aortic group (from 69 +/- 4 mmHg to 65 +/- 13 mmHg; P > 0.05) and coronary sinus group (from 69 +/- 4.6 mmHg to 60 +/- 10 mmHg; P > 0.05). Myocardial relaxation was evaluated by the +/- dp/dt ratio. In the control group there was impairment of myocardial relaxation as indicated by an increase of this index after reperfusion (from 1.05 +/- 0.05 to 1.46 +/- 0.23; P < 0.05), whereas in the aortic (from 1.10 +/- 0.13 to 1.15 +/- 0.20; P > 0.05) and the coronary sinus (from 1.03 +/- 0.14 to 1.08 +/- 0.16; P > 0.05) groups there was no variation. Ultrastructural changes in the myocardium were negligible in all three groups at the end of reperfusion.4. We conclude that intermittent perfusion of a hypothermic cardioplegic solution through the coronary sinus is effective for the protection of the myocardium during total ischemia.
Keywords: CARDIOPLEGIA; RETROPERFUSION; RETROGRADE SINUS PERFUSION; MYOCARDIUM PROTECTION